Pemberdayaan Ekonomi Rumah Tangga melalui Pelatihan Pembuatan Nugget Sayuran untuk Ketahanan Ekonomi Masyarakat Berisiko Stunting - Usman, Moneyzar; Darmawan, Arif; Rahmalia, Dian; Safitri, Tina (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
The family's economic inability to fulfill basic food needs is one of the causes of stunting, which inhibits child growth and development. This encourages every family in the community to emphasize the importance of strengthening the household economy. Effective household economic management contributes to the fulfillment of family nutrition, in line with improved consumption patterns based on socioeconomic status. This activity is located in Way Gelam Village, Candipuro Sub-district, where the Women Farmers Group (KWT) in the village utilizes yard vegetables as the main commodity developed by the local community. This is also a strong basis for developing value-added products, one of which is vegetable nuggets. The purpose of this service is to increase household economic capacity through KWT empowerment and encourage vegetable consumption to reduce the risk of stunting due to malnutrition. The methods used include surveys, FGDs, observations, and demonstrations. The results of this service activity include partners gaining knowledge and assistance in making vegetable nuggets. A total of 100% of partners expressed satisfaction that the Service team provided services and assistance that suited their needs.